A Review of the Effects of the Violence Against Women Act on Law Enforcement - Jennings, Wesley G. (Violence against women, 2021)
One of the goals of the Violence Against Women Act (VAWA) was to improve law enforcement responses to sexual and domestic violence by providing funding to expand prevention, enhance investigations, and increase victim services. Since VAWA’s enactment, police responses to these crimes have evolved, including officer responses to victims and offenders, and various agency operations. This article highlights some noteworthy changes in law enforcement related to facilitating victim reporting, enhancing victim advocacy and services, crime reduction and investigative tools, supplementing personnel and training, and encouraging multiagency collaborations as a result of VAWA.